Non-invasive brain stimulation as add-on therapy for subacute post-stroke aphasia: a randomized trial (NORTHSTAR). (December 2020) - Zumbansen, Anna; Black, Sandra E; Chen, Joyce L; J Edwards, Dylan; Hartmann, Alexander; Heiss, Wolf-Dieter; Lanthier, Sylvain; Lesperance, Paul; Mochizuki, George; Paquette, Caroline; Rochon, Elizabeth A; Rubi-Fessen, Ilona; et al.
Introduction: Non-invasive brain stimulation (NIBS) with speech therapy might improve recovery from post-stroke aphasia. This three-armed sham-controlled blinded prospective proof-of-concept study tested 1 Hz subthreshold repetitive transcranial magnetic stimulation (rTMS) and 2-mA cathodal transcranial direct current stimulation (ctDCS) on the right pars triangularis in subacute post-stroke aphasia. Patients and methods: Sixty-three patients with left middle cerebral artery infarcts were recruited in five hospitals (Canada/United States/Germany, 01–2014/03–2018) and randomized to receive rTMS ( N = 20), ctDCS ( N = 24) or sham stimulation ( N = 19) with ST for 10 days. Primary outcome variables were Z -score changes in naming, semantic fluency and comprehension tests and adverse event frequency. Secondary outcome variable was the percent change in the Unified Aphasia Score. Intention-to-treat analyses tested between-group effects at days 1 and 30 post-treatment with a pre-planned subgroup analysis for lesion location (affecting Broca's area or not). Results: Naming was significantly improved by rTMS (median = 1.91/interquartile range = 0.77/ p = .01) at 30 days versus ctDCS (median = 1.11/interquartile range = 1.51) and sham stimulation (median = 1.02/interquartile range = 1.71). All other primary results were non-significant. The rTMS effect was driven by the patient subgroup with intact Broca's area where NIBS tended to improve UnAS (median = 33.2%/interquartile range = 46.7%/ p = .062) versus sham stimulation (median = 12.5%/interquartile range = 7.9%) at day 30. Conversely, in patients with infarcted Broca's area, UnAS tended to improve more with sham stimulation (median = 75.0%/interquartile range = 86.9%/ p = .053) versus NIBS (median = 12.7%/interquartile range = 31.7). Conclusion: We found a delayed positive effect of low-frequency rTMS targeting the right pars triangularis on the recovery of naming performance in subacute post-stroke aphasia. This intervention may be beneficial only in patients with morphologically intact Broca's area.